A RARE MANUSCRIPT OF DEVON OF KHOLIS (TAMADDUN NURI JURNALI, 2024)
This article describes one of Kholis’s rare divans, who lived and created in the late 19th and early 20th centuries. Information about the Devonian composition is given.